Whole Blood Transcriptome Analysis in Children with Sickle Cell Anemia - Gee, Beatrice E.; Pearson, Andrea; Buchanan-Perry, Iris; Simon, Roger P.; Archer, David R.; Meller, Robert (Frontiers in Genetics, 2022)
Whole transcriptome RNA-sequencing was performed to quantify RNA expression changes in whole blood samples collected from steady state sickle cell anemia (SCA) and control subjects. Pediatric SCA and control subjects were recruited from Atlanta (GA) - based hospitals systems, and consented for RNA sequencing. RNA sequencing was performed on an Ion Torrent S5 sequencer, using the Ion Total RNA-seq v2 protocol. Data were aligned to the hg19 reference genome. 557 genes were differentially expressed between SCA and controls (±1.5 fold change FDR p<0.05) and 590 genes show differential transcript expression (±1.5 fold FDR p<0.05). Differentially expressed RNA are enriched for hemoglobin associated genes and ubiquitin-proteasome pathway genes. Further analysis show higher gamma globin gene expression in SCA (33-fold HBG1 and 49-fold HBG2, both FDR p< 0.05), which did not correlate with hemoglobin F protein levels. eQTL analysis identified SNPs in novel non-coding RNA RYR2 gene as having a potential regulatory role in HBG1 and HBG2 expression levels. Gene expression correlation identified JHDM1D-AS1(KDM7A-DT), a non-coding RNA associated with angiogenesis, enhanced GATA1 and decreased JAK-STAT signaling to correlate with HBG1 and HBG2 mRNA levels. These data identify novel regulatory mechanisms for fetal hemoglobin regulation, which may offer innovative therapeutic approaches for SCA.